The Translator’s Closet: Editing Sexualities in Argentine Literary Culture - Larkosh, Christopher (TTR, 2007)
AbstractThis article attempts to draw a theoretical line between closeted (homo)sexuality and translation through the example of the translational activity of those who collaborated on the 20th-century Argentine literary journal SUR: J. Bianco, E. Pezzoni, V. Ocampo, and H. A. Murena. Through a critical reading of explicit and thinly-veiled discourses on homosexuality in works both written and translated in this period, especially when placed in the context of theoretical discourses on translation, gender and sexuality, it reveals a question all the more unavoidable for present-day discussions: Is translation a closet, and if so, when and how?